Secondary metabolites derived from soft corals uses for chemotaxonomical markers and lead bioactive candidates - Kazuki Tani (2020)
Soft corals are prolific producers of secondary metabolites in the marine ecosystem. T here has been a surge in reports on secondary metabolites of soft corals from the South China Seas. To better understand the diversity of secondary metabolites produced by the Bornean soft corals, we collected a total of 14 populations belonging to the genus Nephthea, Lemnalia, Sarcophyton and Sinularia. Secondary metabolites were isolated and their structures elucidated to understand their unique structural features. Correlations between structure type with populations and sampling location were established using Principal Component Analysis, their suitability as chemo taxonomic markers in comparison with phylogeny data is established. Total of 61 compounds with nine novel entities, except steroids, are represented by nine structure types; 1) iso-propyl (-ene) cembrene, 2) lactone cembrene, 3) furano cembrene, 4) nardosinane, 5) neolemnane, 6) guaiane, 7) germacrene, 8) furano sesquiterpene, and 9) aristolane. Isolated compounds could be classified as; Nephthea spp. with 17 compounds and 3 structure types, Lemnalia spp. with 12 compounds and 4 structure types, Sarcophyton spp. with 15 compounds and 2 structure types, and Sinularia spp. with 21 compounds and 6 structure types. Anti-fungal assay against crustacean pathogens exhibited strongest activities against Exophiala sp., L. thermophilum, H. milfordensis and 0. humicola by compounds 4, 6, 7, 9, 15, and 35, and their MIC were evaluated. In addition, isolated compounds also exhibited anti-inflammation and anti-cancer activities. Compounds 39 and 57 exhibited anti-inflammatory inhibitory effect against LPS-induced RAW 264.7 and their mechanism of actions were evaluated PGEi, T NF-a, IL-1(3, IL-6 production, and expression of iNOS and COX-2. Anti-cancer activity against MCF-7 cell line showed that compounds 9 and 10 possess weak cytotoxicity. Apoptosis mechanism revealed presence of pro-apoptotic protein Bax and P53 activation and anti-apoptotic protein Bcl-2. In conclusion, the present study has revealed that soft corals from Borneo have the capacity to produce a wide array of structurally interesting secondary metabolites in the taxonomic studies. Isolated compounds also exhibited a wide diversity of biological activities and could be promising lead pharmaceuticals.